Randomised controlled trial of pelvic floor muscle training during pregnancy - Salvesen, Kjell Å (BMJ Publishing Group Ltd., 2004)
Objectives To examine a possible effect on labour of training the muscles of the pelvic floor during pregnancy. Design Randomised controlled trial. Setting Trondheim University Hospital and three outpatient physiotherapy clinics in a primary care setting. Participants 301 healthy nulliparous women randomly allocated to a training group (148) or a control group (153). Intervention A structured training programme with exercises for the pelvic floor muscles between the 20th and 36th week of pregnancy. Main outcome measures Duration of the second stage of labour and number of deliveries lasting longer than 60 minutes of active pushing among women with spontaneous start of labour after 37 weeks of pregnancy with a singleton fetus in cephalic position. Results Women randomised to pelvic floor muscle training had a lower rate of prolonged second stage labour (24%, 95% confidence interval 16% to 33%; 22 out of 105 women were at risk (undelivered) at 60 minutes in the survival analysis) than women allocated to no training (38% (37/109), 28% to 47%). The duration of the second stage was not significantly shorter (40 minutes v 45 minutes, P = 0. 06). Conclusions A structured training programme for the pelvic floor muscles is associated with fewer cases of active pushing in the second stage of labour lasting longer than 60 minutes.